Histone Modification Landscapes as a Roadmap for Malaria Parasite Development - Connacher, J.; von Grüning, H.; Birkholtz, L. (Frontiers in Cell and Developmental Biology, 2022)
Plasmodium falciparum remains the deadliest parasite species in the world, responsible for 229 million cases of human malaria in 2019. The ability of the P. falciparum parasite to progress through multiple life cycle stages and thrive in diverse host and vector species hinges on sophisticated mechanisms of epigenetic regulation of gene expression. Emerging evidence indicates such epigenetic control exists in concentric layers, revolving around core histone post-translational modification (PTM) landscapes. Here, we provide a necessary update of recent epigenome research in malaria parasites, focusing specifically on the ability of dynamic histone PTM landscapes to orchestrate the divergent development and differentiation pathways in P. falciparum parasites. In addition to individual histone PTMs, we discuss recent findings that imply functional importance for combinatorial PTMs in P. falciparum parasites, representing an operational histone code. Finally, this review highlights the remaining gaps and provides strategies to address these to obtain a more thorough understanding of the histone modification landscapes that are at the center of epigenetic regulation in human malaria parasites.